The pathogenesis of superior mesenteric artery dissection: An in-depth study based on fluid–structure interaction and histology analysis. (November 2022) - Jia, Zhongzhi; Mei, Junhao; Ding, Wei; Zhao, Xi; Gong, Wen; Yu, Haiyang; Qin, Lihao; Piao, Zeyu; Chen, Wenhua; Tang, Liming
Abstract: Objective: To explore the role of hemodynamic factors in the occurrence of superior mesenteric artery (SMA) dissection (SMAD) using a fluid–structure interaction (FSI) simulation method, and to identify histopathologic changes occurring in the wall of the SMA. Methods: A total of 122 consecutive patients diagnosed with SMAD and 122 controls were included in this study. Hemodynamic factors were calculated using a FSI simulation method. Additionally, SMA specimens obtained from 12 cadavers were stained for histological quantitative analysis. Results: The mean aortomesenteric angle (59.7° ± 21.4° vs 48.2° ± 16.8°; p  < .001) and SMA maximum curvature (0.084 ± 0.078 mm -1 vs 0.032 ± 0.023 mm −1 ; p  < .001) were higher in SMAD patients than the controls. Larger aortomesenteric angles and SMA curvatures were associated with higher and more concentrated wall shear stress at anterior wall of the SMA curve segment, co-located with the dissection origins. The mean thickness of media (325.18 ± 44.87 µm vs 556.92 ± 138.32 µm; p  = .003) was thinner in the anterior wall of the SMA curve than in the posterior wall. The area fractions of elastin (17.96% ± 3.36% vs 27.06% ± 4.18%; p  = .002) and collagen (45.43% ± 6.89% vs 55.57% ± 7.57%; p  = .036) were lower in anterior wall of the SMA curve than in posterior wall. Conclusion: Increased aortomesenteric angle and SMA curvature are risk factors for SMAD. Both of these factors can cause local hemodynamic abnormalities, which can lead to histopathologic changes in anterior wall of SMA.